FINANCING PROGRAMS FOR THE DEVELOPMENT OF ECOLOGICALLY UNFAVORABLE TERRITORIES: ORGANIZATIONAL AND LEGAL FEATURES - Kurbanov, Salman; Zabolotskaia1, Irina; Sekerin, Vladimir (Revista Inclusiones, 2020)
The article examines the methods of state participation in the development of ecologically unfavorable territories, the main of which is the inclusion of ecologically unfavorable territories in the state projects and programs, providing funding and organization of the necessary work. The aim of the presented work is to determine the financing mechanism to restore ecologically unfavorable territories. In particular, in Russia, the amount of planned work does not correspond to the real situation in this area and multiple increases in financial resources from the federal and regional budgets are required to ensure a real positive change in the state of ecologically unfavorable territories. The sources of funding the program activities are considered; a significant place among them is given to various funds to restore and improve the state. It is proposed to direct a part of the income of the extractive industries of the economy, as well as penalties for enterprises that damage the natural environment, for these purposes. At the level of municipal bodies – a fund for the restoration of the ecology of territories, organized at the expense of land tax funds, penalties for enterprises that damage the natural environment, and other sources.